Determination of the detection efficiency of in thiroid using Monte Carlo method - Dayana Ramos Machado; Yoan Yera Simanca; Gladys Mercedes López Bejerano; Nancy Acosta Rodríguez (Nucleus, 2016)
Monte Carlo Method was the base to estimate the detection efficiency of of the identiFINDER ultra detector in “thyroid” geometry. The suitability of the calibration methodology is discussed using a comparison of the results of the Direct Monte Carlo Method and the Transfer Monte Carlo Method calculations with the values of experimentally calculated efficiency. Transfer Monte Carlo Method was the elected methodology because of the differences with the real detection efficiency stay below 10 %. In the simulations, the geometric parameters of the detector were found using a tomography study. The arrangement detector – point source was simulated to obtain the correction factors for preset distances, and the arrangement detector – thyroid phantom was simulated to obtain the detection efficiency curve in function of the distance for . In order to validate the proposed methodology the Internal Dosimetry Laboratory of the Centre for Radiation Protection and Hygiene participated in a regional intercomparison exercise of measured activity estimation in thyroid, for the estimation were used the traditional calculation methodology as well as the methodology base on Monte Carlo Method, the results were satisfactory in both cases. As a final result, the curves of detection efficiency for the measurement of in the thyroid gland was obtained without using physical phantoms, replacing the current lack of it.